PENINGKATAN PENGETAHUAN DAN KEWASPADAAN WARGA TERHADAP KENCING MANIS SERTA DETEKSI DINI KADAR GULA DARAH DI BANJAR PISANG KAJA, DESA TARO - NI WAYAN SEPTARINI (Buletin Udayana Mengabdi, 2014)
Indonesia has been facing double burden of diseases which are communicable and non-communicable diseases. One of the non-communicable disease that recently increase in cases is diabetes which signed by the increase ofglucose level in the blood. This program is aimed to increase knowledge and early detection of diabetes among thehead of household in Pisang Kaja Village, Taro, Tegallalang, Gianyar. The activity started by giving brochure andexplanation about the cause, symptom, and prevent mode of diabetes followed by early detection of blood sugarlevel, weight and blood pressure measurement. The blood sugar level of participants were between 69-194 mg/dland the mean was135.17.The mean (SD) weight, systolic and diastolic blood pressure were 56.53 (8.5) kg; 121.74(13.2) mmHg respectively. There were no cases of diabetes found in this community, that is might be due to highphysical activities as farmers and healthy eating practices. The blood pressures were also within standard normal,even there were few cases of hypertension detected. Lifestyle modification and referrals to the public health care(Puskesmas) offered to these cases. This activity is a good example in early detection on several chronic/non-communicable diseases even though maybe the best place to conduct it in urban area where the lifestyle more sedentary and poor healthy eating practices.Keywords: blood pressure, diabetes mellitus, early detection,and weight